A Novel Method for Synthesis of 3,5-Diaryl Isoxazolines and 3,5-Diaryl Isoxazoles - V.B. Tayade, Miss; Jamode, V.S. (Asian Journal of Chemistry, 2010)
Some new 3,5-diaryl isoxazolines and 3,5-diaryl isoxazoles have been synthesized by a novel method and by short route, 3,5-diaryl 1-phenyl isoxazolines (3) were synthesized by the reaction of 2-hydroxy acetophenones (1) with hydroxylamine hydrochloride in alcohol medium containing a little piperidine. 2-aroyl acetophenones (2) with hydroxylamine hydrochloride in alcohol medium containing a little piperidine produces 3,5-diaryl-1-phenyl isoxazoles (4). Structures of these compounds have been established by spectral analysis (IR, UV and NMR).